Cartilage Tissue Engineering and Regeneration Techniques 2019
DOI: 10.5772/intechopen.84780
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Effect of Medicinal Plants for Cartilage Regeneration

Abstract: Any trauma to a joint such as sports injury can lead to osteoarthritis especially injuries that include torn cartilage, dislocated joints and ligaments. In sports injury specifically, most of the ointments in the market are only applied after physical activity. Repair of the bone and cartilage continues to be a challenge. Autologous and allografts are the gold standard for the treatment of the bone and cartilage. They have an invasive, open surgical procedure that requires the tissue to be harvested from an al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…7 In addition, flavonoids play a role in increasing bone cell viability and bone density. 34,35 Flavonoids also play a role in the proliferation and tissue remodeling phase by increasing vascularization so that there is maximal supply of oxygen and nutrients to the injured cell tissue. Thus, there is an increase in collagen synthesis, thereby accelerating the wound healing process.…”
Section: Discussionmentioning
confidence: 99%
“…7 In addition, flavonoids play a role in increasing bone cell viability and bone density. 34,35 Flavonoids also play a role in the proliferation and tissue remodeling phase by increasing vascularization so that there is maximal supply of oxygen and nutrients to the injured cell tissue. Thus, there is an increase in collagen synthesis, thereby accelerating the wound healing process.…”
Section: Discussionmentioning
confidence: 99%
“…This could be a result of influence due to location and execution of study questionnaire. However, studies have observed that traditional medicine/herbal products are being practiced and used mostly by poor African black communities for their wellbeing [11,23].…”
Section: Discussionmentioning
confidence: 99%
“…Berberine and Icariin promote odontoblastic and odontogenic differentiation, they are both responsible of the inhibition of alveolar bone osteoporosis and promote periodontal bone regeneration [43] [82] [95]- [102], Drynaria iisos increases bone cell viability [103] [104], Rhizoma drynariae enhances the proliferation of hmscs [2] [103] [104], Foeniculum vulgare promotes differentiation of hMSCs into osteoblasts [104], Ferula gummosa has antibacterial effects and induces proliferation of hMSCs into osteocytes [105], Resveratrol induces proliferation and differentiation of articular cartilage, enhances bone healing by its anti-inflammatory properties, responsible for the inhibition of boneloss and increases the blood supply [104] [106]- [111]. Fructus ligustri lucidi increases osteogenesis stimulating genes [112] [113].…”
Section: Action On Alveolar Bonementioning
confidence: 99%